(untitled) (Symposium on Natural and Applied Sciences, 2026)
This article investigates the pedagogical effectiveness of employing authentic materials in teaching to 10-11th grade students, with particular emphasis on the development of core life skills, including communication, critical thinking, collaboration, and problem-solving abilities. Besides, it highlights authentic materials created for real-life communicative purposes that are examined as a means of fostering meaningful language use and enhancing learners’ ability to operate in real-world contexts.